1997
DOI: 10.1177/000348949710601104
|View full text |Cite
|
Sign up to set email alerts
|

Reversibility of Medialization Laryngoplasty an Experimental Study

Abstract: Medialization laryngoplasty has become a routine procedure for cases of unilateral vocal fold paralysis. In certain clinical situations, it may become desirable to reverse the procedure and remove the implant. This process was studied experimentally in eight dogs in a chronic model of induced canine phonation. A silicone polymer implant was inserted to medialize one normal vocal fold for a period of 1 month, after which it was removed. Motion of the cricoarytenoid (CA) joint and induced phonation were studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 26 publications
(7 reference statements)
0
8
0
Order By: Relevance
“…Some authors 47,50 have reported a major fibrous reaction in the silicone implants as well, and attribute it to the greater stability and lesser degree of displacement of the implant. No signs of malignant degeneration were observed in any specimen, but this may have been due to the fact that the study period was relatively short.…”
Section: Comparison Of Silicone and Teflon Resultsmentioning
confidence: 99%
“…Some authors 47,50 have reported a major fibrous reaction in the silicone implants as well, and attribute it to the greater stability and lesser degree of displacement of the implant. No signs of malignant degeneration were observed in any specimen, but this may have been due to the fact that the study period was relatively short.…”
Section: Comparison Of Silicone and Teflon Resultsmentioning
confidence: 99%
“…Revision ML is further complicated by scarring from previous dissection within the paraglottic space for implant placement. While limited fibrosis around a Gore-Tex implant has been shown 20 compared with silastic implants 21 in animal Subjective voice outcomes pre-and postrevision ML have previously been reported by 4 studies. 13,[16][17][18] Subjective voice improvement was noted in 80% of patients by Maragos 13 and Figure 2.…”
Section: Discussionmentioning
confidence: 86%
“…He stressed that this surgical procedure should not be carried out in cases where there was a possibility that nerve function might return. 16 In another investigation, Whitmore compared PETP and e-PTFE as graft material in the sclera of rabbits. While e-PTFE could be easily removed from the capsule-like covering in the sclera, it was observed that PETP was rmly bound to the underlying tissue.…”
Section: Resultsmentioning
confidence: 99%